Non-Watson-Crick base associations in DNA and RNA revealed by single crystal x-ray diffraction methods: Mismatches, modified bases, and nonduplex DNA - Brown, T; Hunter, W (1997)
Single crystal x-ray diffraction methods have been used to characterize numerous oligonucleotide structures, providing valuable information on the fine structure of DNA, oligonucleotide hydration, interactions with small molecule ligands and proteins. There has been a particular focus on nonstandard base associations and a number of groups have sought to characterize different non-Watson-Crick base pairs to further the understanding of their influence on the structure of duplex DNA and RNA, and to investigate which structural features might be utilized by enzymes in recognition and repair of these errors in DNA. Bases that have been chemically damaged by mutagenic or carcinogenic agents have distinctive modified hydrogen-bonding patterns and these have been investigated. The structure determination of a series of nonduplex DNA structures including examples of a triplex, quadruplexes, and a novel DNA loop have recently been published. In this article we survey the structures of a series of non-Watson-C rick base associations in duplex DNA and RNA. We show how nonstandard base pairs. base triads, and tetrads play an important role in stabilizing nonduplex structures. © 1997 John Wilev and Sons, Inc.